2023
DOI: 10.1163/15685381-bja10138
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the critically endangered Karpathos water frog (Anura, Amphibia): conservation insights from complete mitochondrial genome sequencing

Abstract: The Karpathos water frog (Pelophylax cerigensis) is classified as Critically Endangered according to the IUCN Red List and its distribution is restricted on the island of Karpathos, South Aegean Sea. Utilizing a next generation sequencing approach, we obtained whole mitochondrial genomes of P. cerigensis to determine the species phylogenetic position within the genus Pelophylax and to clarify the phylogenetic relationship between the species’ population on Karpathos Island and the population of P. cf. bedriaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As a consequence, a proper overview of the evolution, diversity and distribution of the genus remains genuinely lacking. Mitochondrial DNA (mtDNA) has been preferentially sequenced to identify and map phylogeographic lineages, but mtDNA sequences are scattered across more than a hundred publications that vary in taxonomic scales, geographic scopes, sets of genes analyzed, and further differ in the way these lineages are delimited, labelled and taxonomically treated (e.g., Akın et al., 2010; Bellati et al., 2023; Bülbül et al., 2011; Dufresnes, Di Santo, et al., 2017; Hoffmann et al., 2015; Komaki et al., 2015; Liu et al., 2010; Lymberakis et al., 2007; Min et al., 2008; Nicolas et al., 2015; Papežík et al., 2023; Plötner et al., 2008; Svinin et al., 2021; Toli et al., 2023; Ualiyeva et al., 2022; Wang et al., 2017). Moreover, mitochondrial barcoding may not be reliable due to hybridization, that cause mitochondrial transfer between sympatric and parapatric species (e.g., Doniol‐Valcroze et al., 2021; Komaki et al., 2015; Liu et al., 2010), including the parental species of hybridogenetic hybrids (Plötner et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a proper overview of the evolution, diversity and distribution of the genus remains genuinely lacking. Mitochondrial DNA (mtDNA) has been preferentially sequenced to identify and map phylogeographic lineages, but mtDNA sequences are scattered across more than a hundred publications that vary in taxonomic scales, geographic scopes, sets of genes analyzed, and further differ in the way these lineages are delimited, labelled and taxonomically treated (e.g., Akın et al., 2010; Bellati et al., 2023; Bülbül et al., 2011; Dufresnes, Di Santo, et al., 2017; Hoffmann et al., 2015; Komaki et al., 2015; Liu et al., 2010; Lymberakis et al., 2007; Min et al., 2008; Nicolas et al., 2015; Papežík et al., 2023; Plötner et al., 2008; Svinin et al., 2021; Toli et al., 2023; Ualiyeva et al., 2022; Wang et al., 2017). Moreover, mitochondrial barcoding may not be reliable due to hybridization, that cause mitochondrial transfer between sympatric and parapatric species (e.g., Doniol‐Valcroze et al., 2021; Komaki et al., 2015; Liu et al., 2010), including the parental species of hybridogenetic hybrids (Plötner et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic studies based on one or two mitochondrial genes [6,7,15,17) and complete mitogenomes [16] revealed that P. cerigensis occurs on Karpathos Island but is also present in Rhodes Island. Interestingly, Akın et al [7] and Akın Pekşen [17] indicated that all P. cerigensis specific haplotypes from Karpathos, Rhodes and southwestern Anatolia formed a single monophyletic group.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, both mtDNA and nuclear marker [17] showed that Karpathos and Rhodes Islands and mainland populations of P. cerigensis are closely related. Because of their restricted range and moderate genetic diversity of P. cerigensis population in southwestern Anatolia, they should be a considered as a third Management Unit (MUs) in addition to those as previously suggested for Karpathos and Rhodes populations [16]. It is crucial to develop and implement appropriate conservation strategies to assure future survival and conservation of these threatened P. cerigensis populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation